Pengaruh Pemenuhan Kebutuhan Karyawan Terhadap Komitmen Kerja Di Bank Muamalat KCU Makassar - Muhammad Fajar; Tenri S. P. Dipoatmodjo; Zainal Ruma; Uhud Darmawan Natsir; Rezky Amalia Hamka (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to determine and analyze the partial and simultaneous influence between Fulfillment of Employee Needs using Maslow's needs theory on Work Commitment to Employees at Bank Muamalat KCU Makassar. This research is an explanatory research with a quantitative approach. This sampling method uses simple random sampling technique with a total sample calculation from the population of permanent employees of Bank Muamalat KCU Makassar, with a sample size of 55 respondents. Data collection was carried out by distributing questionnaires via google form (online) and direct distribution (offline). The data analysis technique used to analyze the relationship between the independent variable and the dependent variable is validity test, reliability test, classical assumption test, namely normality test, multicollinearity test, heteroscedasticity test and linearity test, hypothesis testing used is the coefficient of determination (R2), Partial Test (t test), Simultaneous Test (F test) and Multiple linear regression analysis. The results of this study indicate that physiological needs, security needs, appreciation needs and self-transcendence needs partially have no significant effect on work commitment with a significant value respectively, (physiological needs: 0.810> 0.05), (security needs: 0.979> 0.05), (appreciation needs: 0.093> 0.05) and (self-transcendence needs: 0.400> 0.05), so that hypotheses H1, H2, H4, and H6 are rejected. While social needs and self-actualization needs have a positive and significant effect on work commitment with their respective values, social needs of 0.014 < 0.05 and self-actualization needs of 0.001 < 0.05, so that H3 and H5 are accepted. The results of this study also found that the variable Fulfillment of Needs (physiological needs, security needs, social needs, appreciation needs, self-actualization needs and self-transcendence needs) has a significant simultaneous / joint influence on employee work commitment at Bank Muamalat KCU Makassar based on the results of the F test which is worth 25.101> 2.29 F table values and a significance value of 0.000 <0.05. This means that the fulfillment of physiological needs, security needs, social needs, appreciation needs, self-actualization needs and self-transcendence needs has an important role in increasing the work commitment of employees of Bank Muamalat KCU Makassar.